Insecticides for mediterranean fruit fly control in orange fruits: laboratory and field assessments - Oscar Arnaldo Batista Neto e Silva; Cristiane Müller; Mario Henrique Dal Pogetto; Wagner da Rosa Harter; Cristiane Gindri Manzoni; Larissa Pasqualotto; Matheus Rakes; Daniel Bernardi (Ciência Rural)
ABSTRACT: This study evaluated the toxicity of the insecticide spinetoram at different doses [1.25, 1.87, 2.5, 3.75 and 5.0 g of active ingredient/100 L of water - (g of a.i./100 L)] on adults and larvae of C. capitata. Based on the LC50 and LC90 values, spinetoram showed high toxicity against C. capitata adults in the ingestion bioassay (LC50 = 1.95 and LC90 = 5.10 µg a.i./mL) and topical application (LC50 = 3.10 and LC90 = 8.10 µg a.i./mL), and was statistically superior to acetamiprid + etofenprox (ingestion: LC50 = 5.87 and LC90 = 12.04 µg a.i./mL; topical application: LC50 = 14.05 and LC90 = 21.06 µg a.i./mL). However, spinetoram was less toxic than Chlorpyrifos (ingestion: LC50 = 0.95 and LC90 = 3.06 µg a.i./mL; topical application: LC50 = 0.67 and LC90 = 2.45 µg a.i./mL). At a dose of 5.0 g of a.i./100 L, spinetoram was highly toxic against the 1st, 2nd, and 3rd larval instars in immersion bioassays (80% larval mortality). However, it was not effective against larvae inside the fruits when applied via direct spraying in the region opposite to the sites of oviposition by C. capitata. In contrast, spinetoram (5.0 g a.i./100 L) and chlorpyrifos reduced larval viability when applied directly to the oviposition region. In the field, after three applications at intervals of 14 days, spinetoram (5.0 g a.i./100 L) and chlorpyrifos (96 mL a.i./100 L) reduced damage in orange fruits by more than 95%. According to the results, the insecticide spinetoram can be an alternative to chlorpyrifos and acetamiprid + etofenprox for the control of C. capitata.